“Never give up.” Adjudicated girls’ school experiences and implications for academic success - Laura M. Hopson; Jennifer L. Kenney; Wesley T. Church II; Jill Beck (International Journal of School Social Work, 2022)
There is limited literature on best practices for promoting academic success for adjudicated girls. The goal of this qualitative study was to elicit information about the educational experiences of female juvenile offenders within a residential facility. Interviews with 10 girls and two teachers were audio-recorded and transcribed. Data were analyzed for narratives pertaining to success stories and challenges the girls faced in educational settings. Themes were: Barriers in school; Individual Characteristics that Promote Success; Coping Skills; Relationships that Promote Success; School Environments that Promote Success; Transitioning to Traditional Schools. Findings inform strategies to promote academic success for detained youth. The authors discuss implications for school social workers and other school-based behavioral health providers.
Keywords: Incarcerated Youth; Girls; Academic Outcomes; Social Services in Schools